2021
DOI: 10.3168/jds.2021-20292
|View full text |Cite
|
Sign up to set email alerts
|

Cheese quality from cows given a tannin extract in 2 different grazing seasons

Abstract: The aim of the present study was to compare the effect of dietary tannins on cow cheese quality in 2 different grazing seasons in the Mediterranean. Two experiments were performed on 14 dairy cows reared in an extensive system. The first experiment took place in the wet season (WS), and the second experiment took place in the dry season (DS). In the WS and DS experiments, cows freely grazed green pasture or dry stubbles, respectively, and the diet was supplemented with pelleted concentrate and hay. In both exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
1
6
0
1
Order By: Relevance
“…Animal models included were sheep (2 papers), cows (9 papers) and goats (4 papers). Some studies also reported the progeny of the animals such as primiparous (Safari et al ., 2018; Li et al ., 2021) and multiparous (Hausmann et al ., 2018; Safari et al ., 2018; Li et al ., 2021; Wang et al ., 2021) and included the period of lactation (Ianni et al ., 2019, 2021; Bonanno et al ., 2019b; Mapato et al ., 2021; Menci et al ., 2021) or specified mid-lactation (Scuderi et al ., 2019; Simitzis et al ., 2019). Design of the studies included randomized (Cais-Sokolińska et al ., 2015; Hausmann et al ., 2018; Safari et al ., 2018; Ianni et al ., 2019; Bonanno et al ., 2019a; Walkenhorst et al ., 2020; Li et al ., 2021; Wang et al ., 2021), stratified (Scuderi et al ., 2019; Walkenhorst et al ., 2020), allocated (Delgadillo-Puga et al ., 2019; Simitzis et al ., 2019) and 4 × 4 Latin square design with a 2 × 2 factorial arrangement (Mapato et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Animal models included were sheep (2 papers), cows (9 papers) and goats (4 papers). Some studies also reported the progeny of the animals such as primiparous (Safari et al ., 2018; Li et al ., 2021) and multiparous (Hausmann et al ., 2018; Safari et al ., 2018; Li et al ., 2021; Wang et al ., 2021) and included the period of lactation (Ianni et al ., 2019, 2021; Bonanno et al ., 2019b; Mapato et al ., 2021; Menci et al ., 2021) or specified mid-lactation (Scuderi et al ., 2019; Simitzis et al ., 2019). Design of the studies included randomized (Cais-Sokolińska et al ., 2015; Hausmann et al ., 2018; Safari et al ., 2018; Ianni et al ., 2019; Bonanno et al ., 2019a; Walkenhorst et al ., 2020; Li et al ., 2021; Wang et al ., 2021), stratified (Scuderi et al ., 2019; Walkenhorst et al ., 2020), allocated (Delgadillo-Puga et al ., 2019; Simitzis et al ., 2019) and 4 × 4 Latin square design with a 2 × 2 factorial arrangement (Mapato et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Design of the studies included randomized (Cais-Sokolińska et al ., 2015; Hausmann et al ., 2018; Safari et al ., 2018; Ianni et al ., 2019; Bonanno et al ., 2019a; Walkenhorst et al ., 2020; Li et al ., 2021; Wang et al ., 2021), stratified (Scuderi et al ., 2019; Walkenhorst et al ., 2020), allocated (Delgadillo-Puga et al ., 2019; Simitzis et al ., 2019) and 4 × 4 Latin square design with a 2 × 2 factorial arrangement (Mapato et al ., 2021). Dairy products evaluated in different studies included kefir (Cais-Sokolińska et al ., 2015), milk (all other papers) and, additionally, cheese (Ianni et al ., 2019; Bonanno et al ., 2019a, 2019b; Menci et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations